Cough in the community: a cross sectional survey and the relationship to gastrointestinal symptoms. Issue 11 (29th June 2006) - Ford, A C; Forman, D; Moayyedi, P; Morice, A H
Abstract : Background: The prevalence and severity of chronic cough in the community is uncertain. In a large population of representative normal subjects, we explored the relationship between self-reported cough severity and frequency, and factors known to be related to the aetiology of chronic cough. In particular, we have examined the relative association between cough and symptoms of gastrointestinal disease. Methods: A cross-sectional survey was undertaken in 36 general practices with subjects randomly selected from practice computer databases. Baseline lifestyle and demographic characteristics were recorded. Participants were asked how often in the previous 2 months they had experienced bouts or spasms of coughing. Cough symptom status was dichotomised into symptomatic using a cut off of bouts or spasms of coughing at a frequency of between once a week and once a day or above. Gastrointestinal data were collected using validated methodology. Results: Questionnaires were sent to 6416 subjects and 4003 (62%) responded. The prevalence of chronic cough was 12%, and was severe in 7%. Following multivariate analysis, regurgitation (OR 1.71; 99% CI 1.20 to 2.45) and irritable bowel syndrome (OR 2.00; 99% CI 1.47 to 2.72) were strong predictors of cough. Smoking (OR 1.61; 99% CI 1.18 to 2.19), declining social class (OR 1.63; 99% CI 1.04 to 2.57), and quality of life at baseline (OR 1.63; 99% CI 1.13 to 2.35) were also significantly associated. Conclusion: Chronic cough is a common symptom in the general population. Its strong association with gastrointestinal disease may have aetiological significance.